New records and morphological assessments of long-nosed fruit bats (chiroptera: pteropodidae: Macroglossus spp.) from Vietnam - Thanh, Hoang Trung; Son, Nguyen Truong; Duong, Vu Thuy; Luong, Nguyen Thanh; Loi, Dao Nhan; Thong, Vu Dinh (Academia Journal of Biology, 2019)
Long-nosed fruit bat is a common name of the genus Macroglossus which comprises two species: Dagger-toothed long-nosed fruit bat (M. minimus) and Greater long-nosed fruit bat (M. sobrinus). These two species were rarely recorded from Vietnam or neighboring countries. Within Vietnam, M. minimus has been recorded only from two localities in southern Vietnam while M. sobrinus was known from all northern, central and southern regions of the country. Morphological features of these species in Vietnam were poorly documented in previous publications. With results from a rapid examination of all specimens and recently captured individuals, we here confirm that M. sobrinus is distinctively larger than M. minimus in all external and craniodental measurements. Two species are also distinguishable by their nostril shapes and mandible symphyses. This paper provides new distributional records of both M. sobrinus and M. minimus from Vietnam with remarks on their ecology and habitats.